Cytogenetic investigations of solid tumours of children. Issue 9 (September 1988) - Pearson, A D; Reid, M M; Davison, E V; Bown, N; Malcolm, A J; Craft, A W
Abstract : The association of non-random chromosome abnormalities with solid tumours of childhood may improve accuracy of diagnosis and prognosis and lead to a better understanding of their biology. In a pilot study in the Northern region of England fresh tumour biopsy specimens were obtained from 39 to 72 consecutive solid tumours in children who presented over a period of 21 months. Cytogenetic analysis was possible in 33 and clonal chromosomal abnormalities were detected in nine. In addition, seven of 10 tumours investigated after treatment were abnormal. Ten of these 16 abnormal karyotypes have not previously been described. This pilot study has shown that a concerted investigation of tumour cytogenetics is possible. A multicentre study is essential if our knowledge of basic tumour cytogenetics is to progress.